Assessment of Knowledge, Attitudes, and Factors Influencing the Selection Student of Generic Medicine - Mohamed N. Al-Arifi (Frontiers Media S.A., 2021)
Background: Generic replacements for branded medicines have become a typical practice among registered pharmacists all over the world. Therefore, this study was aimed to determine the influence of the knowledge and attitudes of PharmD students and other factors on the selection of unbranded medicines.Methods: A descriptive, cross-sectional study was conducted through Google Forms to collect data using self-reported questionnaires. The data was collected over a period of 3 months, from January to March 2021, among junior level pharmacy students who are currently undertaking a PharmD course at the King Saud University, College of Pharmacy, Riyadh, Saudi Arabia.Results: The mean age of the students was 21.05± (SD = 1.03), majority of students 70.2% (n = 134) were able to define the term generic medicine, and about 65% (n = 123) were able to correctly define bioequivalence. More than half of the students, 56.5% (n = 108) lacked knowledge about the pharmacokinetic parameters of generic products. Meanwhile, the majority, 85% (n = 122), supported generics over branded medicines, and about 66% (n = 99) agreed that wider use of generic medicines would lead to less money required for the research and development of new pharmaceuticals.Conclusion: Findings revealed that most pharmacy students possess sufficient knowledge of generic medicines, although knowledge in some aspects remains lacking.